Experimental Investigation on the Mechanical Properties of Glass Fiber Reinforced Nylon - Nuruzzaman, D. M.; Iqbal, AKM Asif; A. N., Oumer; Ismail, N. M.; Basri, S. (IOP Publishing Ltd., UK, 2016)
In this study, the influence of different weight percentages of glass fiber (GF) reinforcement on the mechanical properties of nylon (PA6) composite is investigated. Test specimens of pure nylon, 95% nylon + 5% GF, 90% nylon + 10% GF, 85% nylon + 15% GF and 80% nylon + 20% GF are prepared using an injection molding machine. In the experiments, tensile tests and impact tests are carried out. The obtained results reveal that mechanical properties of the nylon composites are significantly influenced by the weight percentage of glass fiber. From the tensile test results, it is observed that pure nylon has the lowest elastic modulus and yield strength whereas 80% nylon + 20% GF composite shows the highest elastic modulus and yield strength. Moreover, pure nylon shows the lowest tensile strength while 80% nylon + 20% GF shows significantly improved tensile strength. Results show that elongation at break is remarkably high for pure nylon whereas it is very low for 80% nylon + 20% GF. Izod impact test results reveal that, 85% nylon + 15% GF composite has the highest impact strength or toughness whereas 95% nylon + 5% GF composite shows the lowest impact strength. Furthermore, 80% nylon + 20% GF composite shows somewhat less impact strength or toughness than 85% nylon + 15% GF composite.